Leadership dynamics and the use of ICT in the 2015 #FeesMustFallprotests: A comparative analysis of the #WitsFeesMustFall and #UPrising movements (Journal of Student Affairs in Africa, 2026)
The #FeesMustFall movement is often portrayed as having been a singular movement. However, drawing on participant observation, in-depth interviews, online sources and documents, this article undertakes a comparative analysis between two #FeesMustFall formations: #WitsFeesMustFall at the University of the Witwatersrand and #UPrising at the University of Pretoria. It contends that the 2015 #FeesMustFall protests emerged and functioned through multiple campus-specific hashtags that reflected localised institutional concerns. The article reveals similarities and differences within the two movements through two broad perspectives, the use of Information and Communication Technology (ICT) and organisational leadership dynamics. Drawing from the Resource Mobilisation Theory (RMT), the article reveals the centrality of ICT tools, Twitter, Facebook and WhatsApp, in mobilising material and human resources. Furthermore, through an analysis of leadership dynamics, it illustrates how the movements formed, implemented their mandates, fragmented and ultimately dissolved.
Keywords: Fees must fall; social media; student protests; social movements; resource mobilisation; student leaders; South Africa